HIGH-PERFORMANCE LINEAR TO LINEAR POLARIZATION CONVERTER EXHIBITING 30° ANGULAR STABILITY - Haneef Hamza,; Arbab Talha,; Dr. Sadiq Ullah, (Spectrum of Engineering Sciences, 2025)
A thin linear polarization converting metasurface has been proposed with better efficiency and performance. The proposed surface is etched on 3mm thick dielectric substrate. It has the ability to convert linear to orthogonal equivalent in the 10.5-21.5GHz band with polarization conversion ratio above 90%.along with this, parametric analyses has also been conduct to monitor the effect of various parameter on the performance of surface. Moreover, for deeper insight into polarization conversion mechanism the surface current distribution is carried out.